The Aesthetics of Arabic Calligraphy and the Materials Used in Crafting Traditional Art - Alashari, Duaa Mohammed (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2025)
The art of Arabic calligraphy is particularly concerned with the value of beauty and therefore requires specific tools and materials for its writing, formulation, and production. The writing of Arabic calligraphy, both ancient and modern, has been linked to fixed geometric rules and specific tools. Therefore, this paper aims to identify the most prominent materials and tools used in writing it in the past. This study also aims to identify the most important basic rules that calligraphers must follow. The methodology used in this study is historical and descriptive, as it aligns with the study's objectives and goals. One of the most important findings of the study is that the Ottoman calligraphy school developed calligraphy writing tools, beginning with paper, reeds, and knives used for sharpening pens. The study also concluded that each of the tools used in the past in writing Arabic calligraphy is of immense importance, as they form the foundation of the calligraphic work and the essence of its existence.